2021
DOI: 10.47738/ijaim.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Location-Based Mobile Community Using Ants-Based Cluster Algorithm

Abstract: A location based service (LBS) is widely used on modern smartphone around the world asits built-in features. Each smartphone can access a google API or map. People can therefore share their location (latitude and longitude) among friends. Many LBS spots can easily form “location based mobile community (LBMC).” Since the nodes are mobile, the community group changes dynamically and is unstructured. Ant-based clustering algorithm is a special kind of optimization technique which is highly suitable for finding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…By combining ant clustering algorithm and K-means, the clustering problem can converge faster and more efficient. Also, previous study found that ant K-means is a stable performing algorithm for solving a various industrial clustering problems with more promising results [26], [27].…”
Section: Clustering Processmentioning
confidence: 95%
“…By combining ant clustering algorithm and K-means, the clustering problem can converge faster and more efficient. Also, previous study found that ant K-means is a stable performing algorithm for solving a various industrial clustering problems with more promising results [26], [27].…”
Section: Clustering Processmentioning
confidence: 95%
“…Furthermore, for the implementation of Instagram Ads at CV Media Computindo, it is important to adapt to the company's characteristics and goals [20,21]. By understanding the target audience, creating engaging content, and executing effective campaign management, CV Media Computindo can leverage the potential of Instagram Ads to enhance brand awareness and achieve desired outcomes.…”
Section: Figure 1 Business Model Canvas Of CV Media Computindomentioning
confidence: 99%
“…Simultaneously, the research employs traditional methods such as Simple Average (SA), Moving Average (MA), Simple Exponential Smoothing (SES), Double Exponential Smoothing (DES), and Triple Exponential Smoothing (TES) to compute average gold prices. These techniques provide a nuanced understanding of the broader spectrum of prediction methodologies, each contributing unique analytical perspectives [12][13][14] [15].…”
Section: Comparative Analysis Of Prediction Algorithmsmentioning
confidence: 99%
“…This research aims to determine the best algorithm for predicting gold prices using various methods such as Linear Regression (LR), Naive Bayes (NB), Simple Average (SA), Moving Average (MA), Simple Exponential Smoothing (SES), Double Exponential Smoothing (DES), and Triple Exponential Smoothing (TES). Linear regression is used to find a linear relationship between gold prices and other important variables [12][13], while naive bayes is used for classifying the class of an object based on its attributes [14] [15]. Other methods like SES, DES, and TES are employed to calculate the average gold prices from the collected data.…”
Section: Introductionmentioning
confidence: 99%